Analyzing the marketing practices of BSRM in the A steel industry: a study on the impact of digital marketing on customer engagement and brand loyalty - Mazumder, Avranil (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.